2022
DOI: 10.1007/s10664-021-10115-0
|View full text |Cite
|
Sign up to set email alerts
|

A teamwork effectiveness model for agile software development

Abstract: Teamwork is crucial in software development, particularly in agile development teams which are cross-functional and where team members work intensively together to develop a cohesive software solution. Effective teamwork is not easy; prior studies indicate challenges with communication, learning, prioritization, and leadership. Nevertheless, there is much advice available for teams, from agile methods, practitioner literature, and general studies on teamwork to a growing body of empirical studies on teamwork i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 82 publications
1
19
0
1
Order By: Relevance
“…learning-by-doing) enhances team creativity and the effect of learning persists over time. Moreover, Lyndon et al (2020) examined the association between shared leadership, where the leadership function is distributed among members of the team which is a phenomenon characteristic of teams working on agile-based projects (Strode et al, 2022) and team creativity and found team learning to fully mediate this relationship. Finally, team learning orientation and knowledge sourcing were both found to be positively and significantly related to the creativity of information software development project teams (Khedhaouria and Ribiere, 2013).…”
Section: Agile Project Management As a Space For Creativitymentioning
confidence: 99%
“…learning-by-doing) enhances team creativity and the effect of learning persists over time. Moreover, Lyndon et al (2020) examined the association between shared leadership, where the leadership function is distributed among members of the team which is a phenomenon characteristic of teams working on agile-based projects (Strode et al, 2022) and team creativity and found team learning to fully mediate this relationship. Finally, team learning orientation and knowledge sourcing were both found to be positively and significantly related to the creativity of information software development project teams (Khedhaouria and Ribiere, 2013).…”
Section: Agile Project Management As a Space For Creativitymentioning
confidence: 99%
“…On the other hand, agile teamwork refers to the team's stand-up meetings and retrospective meetings that are essential for successfully implementing agile practices (Strode et al, 2022). Stand-up meetings are daily short meetings of the team to discuss new development in their tasks, hurdles that hamper team members from completing tasks, monitor the progress and discuss difficulties in their tasks (Singh and Strobel, 2022).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Previous research accentuated the investigation of the role of agile practices in teams (Karlsen et al, 2022). In particular, agile taskwork has been considerably identified as a predictor of team performance (Strode et al, 2022). Empirical studies in the IT industry show that agile taskwork can significantly impact team performance (Venkatesh et al, 2020;Malik et al, 2021).…”
Section: Agile Work Practices and Team Performancementioning
confidence: 99%
See 1 more Smart Citation
“…DevOps is an Agile approach for Software development, so it is considered to improve team communication, release speed and design flexibility [28], beside teamwork effectiveness [29]. The constant collaboration and the broader perspective of members instigate those teams to be selforganizing, one of Agile Manifesto's principles [30].…”
Section: Discussionmentioning
confidence: 99%